Pengaruh Akuntabilitas Dan Transparansi Terhadap Pengelolaan Dana Desa - Sumiati Rahmawati; Andri Indrawan (AKUNTANSI 45, 2024)
This study aims to determine the effect of accountability and transparency on the management of village funds. The type of research used in this study is quantitative research. The population in this study were employees from villages in Parakansalak sub-district, namely Sukakersa village, Sukatani village, and Parakansalak village, totaling 63 people. the sample in this study were village government administrators and administrators of village institutions and organizational units related to the management of village funds totaling 62 people. In this study sampling with saturated sampling technique. The data collection technique used is primary data. The analysis technique used validity and reliability tests, classical assumption tests, multiple linear regression analysis and hypothesis testing. the results showed that the research data were normally distributed, based on the normality test, multicollinearity test, and heteroscedasticity test, no deviations were found. this indicates that the available data have met the requirements for using multiple linear regression models. the results showed that the accountability variable had a significant effect on the management of village funds and the transparency variable had a significant effect on the management of village funds. meanwhile, simultaneously accountability and transparency had a significant effect on the management of village funds.